PENGEMBANGAN MEDIA POSTER PENDIDIKAN KARAKTER DI SEKOLAH PENDIDIKAN ANAK USIA DINI DUSUN SALU PATTUNG KABUPATEN MAMUJU - Irmayanti Laurentius; Farida Febriati; Andromeda Valentino Sinaga (STKIP Subang, 2023)
Learning media is closely related to the learning process. Learning media is a tool used by educators or teachers in delivering learning materials so that they are easily understood by students. With the media, the learning process is more interesting and not monotonous. This research and development produces a product in the form of character education poster media at the Early Childhood Education school in Salu Pattung Hamlet, Mamuju Regency. The purpose of this development research is to determine the level of need for character education poster media, to determine the design of character education poster media and to determine the level of validity and practicality of character education poster media. This research uses the type of R&D (Research and Development) research. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). This research was conducted at PAUD Salu Pattung Hamlet, Mamuju Regency. The data sources in this study were 2 validators consisting of material validators and media validators, 7 students and 2 teachers. Data were collected through material expert validation, media validation, limited trial, field trial and teacher response. The results of the observation before this research was conducted stated that poster media is needed in the character education process. While the validation by material and media experts was at a very good qualification, the limited trial and field trial received very good qualifications and the teacher's response was also at a very good qualification. The conclusion of this study is that the level of need for poster media products is needed and has been valid and practical for use in early childhood character education.